The correlation study for parameters in four tuples. (2015) - Song, Fei; Zhang, Yige; An, Zhaoxu; Zhou, Huachun; You, Ilsun
For analysing the characteristics of current internet connections, this paper proposed several analytical schemes to study the correlation of parameters inside four tuples. We extracted the real trace in packet level from campus network border routers. No sampling method is added to maintain the full information. First, different time bins are employed for exploring the single parameter variations comprehensively. Then, the potential association of parameters inside four tuples is investigated two-by-two. Thirdly, three tuples' properties are shown and compared. The significance of source port is also discussed. Following that, the duration and size for connections, i.e., four tuples, are studied. Some interesting observations are presented and explained. The influence of three and four tuples fluctuation is checked based on a new statistical scheme we proposed. Finally, the service type classification of connections and packets are demonstrated, respectively. The distribution properties of different services are also declared. The conclusions summarise several unexpected phenomenon and the future work is pointed out at the end.